2015
DOI: 10.2337/db15-0278
|View full text |Cite
|
Sign up to set email alerts
|

Protein Inhibitor of Activated STAT 1 (PIAS1) Protects Against Obesity-Induced Insulin Resistance by Inhibiting Inflammation Cascade in Adipose Tissue

Abstract: Obesity is associated with chronic low-level inflammation, especially in fat tissues, which contributes to insulin resistance and type 2 diabetes mellitus (T2DM). Protein inhibitor of activated STAT 1 (PIAS1) modulates a variety of cellular processes such as cell proliferation and DNA damage responses. Particularly, PIAS1 functions in the innate immune system and is a key regulator of the inflammation cascade. However, whether PIAS1 is involved in the regulation of insulin sensitivity remains unknown. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 40 publications
1
26
0
Order By: Relevance
“…In addition, PIAS1 can be involved in the differentiation of hematopoietic stem cells and T cells (Zhang et al, 2017). Moreover, PIAS1 is critical for inhibiting inflammation in the lung and adipose (Liu et al, 2016;Liu et al, 2015). Liu et al have indicated that PIAS1 could suppress the level of IL-4 and IL-1β in the NF-κB pathway to inhibit the inflammation in the lung (Liu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PIAS1 can be involved in the differentiation of hematopoietic stem cells and T cells (Zhang et al, 2017). Moreover, PIAS1 is critical for inhibiting inflammation in the lung and adipose (Liu et al, 2016;Liu et al, 2015). Liu et al have indicated that PIAS1 could suppress the level of IL-4 and IL-1β in the NF-κB pathway to inhibit the inflammation in the lung (Liu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, a recent report echoes our finding that PIAS proteins play important roles in regulating metabolic inflammation. Liu et al examined expression patterns of PIAS proteins in adipose tissues in diabetic mice [37]; while PIAS1 levels was down-regulated, PIAS4 expression was up-regulated in db / db mice compared to wild type littermates. In addition, adenovirus-mediated PIAS1 over-expression alleviated inflammation in adipocytes although it remained untested whether PIAS4 depletion would have a similar effect.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that PIAS1 accumulates at sites of DNA double-strand breaks and promotes DNA repair in a human osteosarcoma cell line (U2OS) (15). Although DNA damage presumably accumulates when subcutaneous fat is subjected to metabolic stress, Liu et al (10) report that PIAS1 is significantly reduced in iWAT. This difference may be due to cell context-dependent responses, so further studies will be needed to define the contribution of DNA damage in subcutaneous fat to obesity.…”
mentioning
confidence: 97%
“…1). Using fat transplantation models, Liu et al (10) elegantly show that overexpression of PIAS1 could improve WAT-induced systemic metabolic dysfunction in obese animals. Taken together, these results indicate that PIAS1 is critically involved in the maintenance of systemic homeostasis through the regulation of both insulin sensitivity and inflammation in subcutaneous fat.…”
mentioning
confidence: 99%
See 1 more Smart Citation